The causal relationship between antihypertensive drugs and depression: a Mendelian randomization study of drug targets - Yang, Zixian; Li, Jinshuai; Huang, Peichu; Li, Zhichang; He, Jianfeng; Cai, Dongchun; Lai, Yuzheng (Frontiers in Endocrinology, 2024)
Background: Depression ranks as a leading contributor to the global disease burden. The potential causal relationship between the use of antihypertensive medications and depression has garnered significant interest. Despite extensive investigation, the nature of this relationship remains a subject of ongoing debate. Therefore, this study aims to evaluate the influence of antihypertensive medications on depression by conducting a Mendelian randomization study focused on drug targets. Method: We focused on the targets of five antihypertensive drug categories: ACE Inhibitors (ACEIs), Angiotensin II Receptor Antagonists (ARBs), Calcium Channel Blockers (CCBs), Beta-Blockers (BBs), and Thiazide Diuretics (TDs). We collected single-nucleotide polymorphisms (SNPs) associated with these drug targets from genome-wide association study (GWAS) statistics, using them as proxies for the drugs. Subsequently, we conducted a Mendelian randomization (MR) analysis targeting these drugs to explore their potential impact on depression. Results: Our findings revealed that genetic proxies for Beta-Blockers (BBs) were associated with an elevated risk of depression (OR [95%CI] = 1.027 [1.013, 1.040], p < 0.001). Similarly, genetic proxies for Calcium Channel Blockers (CCBs) were linked to an increased risk of depression (OR [95%CI] = 1.030 [1.009, 1.051], p = 0.006). No significant associations were identified between the genetic markers of other antihypertensive medications and depression risk. Conclusion: The study suggests that genetic proxies associated with Beta-Blockers (BBs) and Calcium Channel Blockers (CCBs) could potentially elevate the risk of depression among patients. These findings underscore the importance of considering genetic predispositions when prescribing these medications, offering a strategic approach to preventing depression in susceptible individuals.